The Influence of Work Motivation and Discipline on The Performance of Employees in Garanangkeke Sub-District, Bantaeng District - Putri Audina; Siti Hasbiah; Zainal Ruma; Agung Widhi Kurniawan; Uhud Darmawan Natsir (Economics and Business Journal (ECBIS), 2023)
This study aims to (1) determine the effect of work motivation on employee performance, (2) determine the effect of work discipline on employee performance, (3) determine the influence of motivation and work discipline jointly on employee performance in the Gantarangkeke sub-district office, Gantarangkeke district, Bantaeng regency. The type of data used in this study is quantitative data obtained from questionnaires that are distributed and related to the problem under study with a sample size of 41 people. Data were analyzed using multiple linear regression analysis with the help of SPSS 23 data processing to prove the hypothesis. The results showed that the work motivation variable obtained t-count 2.552 > t-table 1.685 and a significant value of 0.015 <0.05, then H1 is accepted, which means that the work motivation variable has a positive and partially significant effect on the performance variable. While the work discipline variable obtained t-count 7.189 > t-table 1.685 and a significant value of 0.000 <0.05, then H2 is accepted which means the work discipline variable has a positive and partially significant effect on performance variables. Based on the research results it is known that the performance variable, obtained f-count 35.267, where the value is greater than f-table 3.24. And a significant value of 0.000 indicates that the variables of motivation and work discipline have a positive and significant effect on performance variables together. t-table 1.685 and a significant value of 0.000 <0.05, then H2 is accepted, which means that the work discipline variable has a positive and partially significant effect on performance variables. Based on the research results it is known that the performance variable, obtained f-count 35.267, where the value is greater than f-table 3.24. And a significant value of 0.000 indicates that the variables of motivation and work discipline have a positive and significant effect on performance variables together. t-table 1.685 and a significant value of 0.000 <0.05, then H2 is accepted, which means that the work discipline variable has a positive and partially significant effect on performance variables. Based on the research results it is known that the performance variable, obtained f-count 35.267, where the value is greater than f-table 3.24. And a significant value of 0.000 indicates that the variables of motivation and work discipline have a positive and significant effect on performance variables together.